Level of patient satisfaction with the quality of care offered in health centres of the Kwango Provincial Health Division - NKWAHATA NTAMBU, Richard; MAYAMBA MUNGWELE, Mado; Onoya, Wedi Josue; Nswele Ilundu , Odon; Kasongo Mungongo , Emmanuel; Masimango Gasha , Christophe (Orapuh Journal, 2026)
Introduction Patient satisfaction is an indicator that enables the assessment of the performance, efficiency, and effectiveness of a health facility. It enhances attendance and utilisation of health services. In the health centres of the Kwango Provincial Health Division, patient dissatisfaction with the quality of care has been observed. Purpose The general objective of this study was to determine the level of patient satisfaction with the quality of care offered in health centres. Methods This was a cross-sectional study conducted among 384 patients selected through simple random sampling. The survey method, supported by interview techniques, was used for data collection. The collected data were analysed using SPSS version 26 to generate frequencies and percentages for the parameters explored. Results The results showed that the level of patient satisfaction was low. A total of 196 patients (51%) were satisfied, while 188 patients (49%) were not satisfied with the quality of care received. Conclusion To improve the quality of care in health centres within this Provincial Health Division, it is necessary to enhance patient satisfaction by integrating it as a key performance indicator in monitoring and evaluation processes and by strengthening the supervisory role of health zone management teams over healthcare providers.